Shedding of SARS-CoV-2 for 85 Days in COVID-19 Patients With Type 2 Diabetes Mellitus and Lung Metastasis: A Case Report - Wu, Xiaoheng; Shen, Min; Quan, Hui; Zhang, Xianqin; Xu, Fengcheng; Li, Juan; He, Miao; Pan, Dongmei; Cao, Ling; Yue, Changwu; Liu, Tianhu; Jia, Xu (Frontiers in Medicine, 2022)
Background: COVID-19 (coronavirus disease 2019) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seriously endangers people's lives. The variation in SARS-CoV-2 makes the research and development of vaccines and specific drugs particularly important. However, the prevention and diagnosis of COVID-19 cannot be underestimated in the control of the epidemic. Case presentation: We introduced a 65-year-old female patient who was diagnosed with COVID-19. The SARS-CoV-2 nucleic acid test result of this patient was positive again during treatment. It took 85 days from the first symptom to the final cure. According to the known reports, she is currently the patient with the longest virus shedding in Sichuan Province, China. Due to the patient's special condition, she was treated in four hospitals before and after, and she was diagnosed with type 2 diabetes mellitus(T2DM) and right lung metastatic adenocarcinoma. We fully introduced the patient's epidemiological history, diagnosis, testing, and treatment process. The patient was finally discharged from the hospital under the treatment of antiviral, hypoglycaemic, anti-anxiety, and a combination of Chinese and Western medicine. Conclusions: The epidemic is still rampant, and we should not relax our efforts in the prevention and control of viruses. For the elderly, especially those who are suffering from complications or vulnerable to diseases, it is recommended to extend the observation time. Additionally, medical workers should pay attention to the mental state of patients.